At the Origin of a Worldwide Invasion: Unraveling the Genetic Makeup of the Caribbean Bridgehead Populations of the Dengue Vector Aedes aegypti. (18th December 2017) - Sherpa, Stéphanie; Rioux, Delphine; Goindin, Daniella; Fouque, Florence; François, Olivier; Després, Laurence
Abstract: Human-driven global environmental changes have considerably increased the risk of biological invasions, especially the spread of human parasites and their vectors. Among exotic species that have major impacts on public health, the dengue fever mosquito Aedes aegypti originating from Africa has spread worldwide during the last three centuries. Although considerable progress has been recently made in understanding the history of this invasion, the respective roles of human and abiotic factors in shaping patterns of genetic diversity remain largely unexplored. Using a genome-wide sample of genetic variants (3, 530 ddRAD SNPs), we analyzed the genetic structure of Ae. aegypti populations in the Caribbean, the first introduced territories in the Americas. Fourteen populations were sampled in Guyane and in four islands of the Antilles that differ in climatic conditions, intensity of urbanization, and vector control history. The genetic diversity in the Caribbean was low (He = 0.14–0.17), as compared with a single African collection from Benin (He = 0.26) and site-frequency spectrum analysis detected an ancient bottleneck dating back ∼300 years ago, supporting a founder event during the introduction of Ae. aegypti . Evidence for a more recent bottleneck may be related to the eradication program undertaken on the American continent in the 1950s. Among 12 loci detected as F ST -outliers, two were located in candidate genes for insecticide resistance (cytochrome P450 and voltage-gated sodium channel). Genome–environment association tests identified additional loci associated with human density and/or deltamethrin resistance. Our results highlight the high impact of human pressures on the demographic history and genetic variation of Ae. aegypti Caribbean populations.